PELATIHAN DAN PERAKITAN LAMPU PANEL SURYA BAGI MASYARAKAT OPAK-GREMBYANGAN MADUREJO PRAMBANAN SLEMAN - Setyawan, Gogor Christmass; Budiati, Haeni; Jatmika, Jatmika; Jacobus, Liefson; Dwiputranto, Surjawirawan (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
A program of community service has been implemented, with a focus on designing and producing low-cost, easily-assembled solar panels for the Opak-Grembyangan Madurejo Pramabanan village community. Creation of solar panel lighting systems that are practical to use and are capable of producing up to 100 Watts of electricity. The actions taken serve to introduce people to renewable energy sources, educate them about it, and help with solar panel lighting for the master plan area for village tourism development. Village communities may be equipped with the knowledge and skills necessary to create solar panel lights independently and for mass production after receiving continual mentoring and training. Alternative energy management is a more broad goal to be able to lessen reliance on fossil fuels and create a green tourism sector.